Identification of circulating inflammation cytokines as a mediator of gut microbiota and type 2 diabetes mellitus: a Mendelian randomization study - Xin Zhou; Wenbin Zheng; Wen Kong; Tianshu Zeng (Diabetology & Metabolic Syndrome)
Abstract Background Several studies have suggested that the gut microbiota (GM) may be associated with type 2 diabetes mellitus (T2DM). However, the causal relationship between GM and T2DM and whether inflammatory cytokines act as mediators remain unclear. Aims To investigate the association between GM and T2DM and the proportion of this association that is mediated through inflammatory cytokines. Methods We conducted a bidirectional and mediation Mendelian randomization (MR) study utilizing data from the genome-wide association studies (GWAS) of four sources of GM taxa (MiBioGen consortium, n = 18,340; Dutch Microbiome Project, n = 7,738; German biobanks, n = 8,956; FINRISK 2002, n = 5,959), a meta-analysis of inflammatory proteins (n = 14,824), and European-ancestry T2DM (n = 1,528,967). The inverse variance weighted method was applied as the primary method. And two-step MR was employed to identify potential mediating inflammatory cytokines. Results We found evidence for 28 positive and 20 negative causal effects between multiple sources of GM and T2DM using at least two MR methods. And there were 2 positive and 5 negative causal relationships between cytokines and T2DM using at least two MR methods. The mediation MR analysis found that interferon-gamma (IFN-γ) mediated the causal effects of species Kandleria vitulina on T2DM (proportion mediated = 22.5%, P = 0.022). Conclusion The MR study supports the causal effect between Kandleria vitulina species and T2DM, with a potential mediating role played by inflammatory factor IFN-γ. Such result would serve as evidence for GM-targeted and cytokine-targeted therapy to prevent T2DM.